Who is the Hooligan? The Role of Psychopathic Traits. Issue 4 (3rd April 2021) - Fanti, Kostas A.; Phylactou, Eleni; Georgiou, Giorgos
ABSTRACT: The current study aims to examine associations between distinct psychopathic traits with hooliganism, after controlling for the influence of levels of aggression. In addition, we aim to investigate potential associations between psychopathic traits and the likelihood of being involved in hooliganism as leaders or followers. Data were collected from 473 fans ( M age = 22.24, SD  = 3.90) from five different Cypriot football teams who completed questionnaires assessing distinct dimensions of psychopathy, aggression, and hooliganism. Findings suggested that callous-unemotional traits was the stronger predictor of hooliganism and the only dimension of psychopathy associated with leadership and the likelihood of being arrested due to hooligan activities, after accounting for levels of aggression. In contrast, grandiose-manipulation was not associated with hooliganism. Individuals high on impulsive-irresponsibility were also likely to engage in hooliganism especially as followers. In addition to explaining the different roles hooligans have in organized activities, the current study provides evidence that callous-unemotional traits and impulsive-irresponsibility can be the basis for the development of interventions targeting hooliganism. The majority of prior work on hooliganism is sociological in nature, and current findings provide evidence for the importance of individual characteristics in explaining this adverse phenomenon.